Risk management recommendations for environmental releases of gene drive modified insects - Devos, Y; Mumford, JD; Bonsall, MB; Glandorf, DCM; Quemada, HD (Elsevier, 2021)
The ability to engineer gene drives (genetic elements that bias their own inheritance) has sparked enthusiasm and concerns. Engineered gene drives could potentially be used to address long-standing challenges in the control of insect disease vectors, agricultural pests and invasive species, or help to rescue endangered species. However, risk concerns and uncertainty associated with potential environmental release of gene drive modified insects (GDMIs) have led some stakeholders to call for a global moratorium on such releases or the application of other strict precautionary measures to mitigate perceived risk assessment and risk management challenges. Instead, we provide recommendations that may help to improve the relevance of risk assessment and risk management frameworks for environmental releases of GDMIs. These recommendations include: (1) developing additional and more practical risk assessment guidance to ensure appropriate levels of safety; (2) making policy goals and regulatory decision-making criteria operational for use in risk assessment so that what constitutes harm is clearly defined; (3) ensuring a more dynamic interplay between risk assessment and risk management to manage uncertainty through closely interlinked pre-release modelling and post-release monitoring; (4) considering potential risks against potential benefits, and comparing them with those of alternative actions to account for a wider (management) context; and (5) implementing a modular, phased approach to authorisations for incremental acceptance and management of risks and uncertainty. Along with providing stakeholder engagement opportunities in the risk analysis process, the recommendations proposed may enable risk managers to make choices that are more proportionate and adaptive to potential risks, uncertainty and benefits of GDMI applications, and socially robust.